"Geoenvironmental assessment of the environs of the Aluminium Smelting Company in Ikot Ahasi, southeastern Nigeria " (2009)
" The Aluminium Smelting Company, located in Ikot Abasi area, lies within the dominantly clastic rocks of the Benin Formation of the eastern Niger Delta. In order to evaluate the level of environmental contamination associated with this major industrial project, concentrations of trace elements and major elements in representative samples of soil, stream sediments and water in the vicinity of the industrial complex were determined by ICP-OES (for soil and stream sediments) and Atomic Absorption Spectrophotometer (AAS) (for water). Samples from a control site, about 3km from the complex were also collected and analyzed for the same set of elements, Results revealed that concentrations of all the elements in the sampled materials were within background levels in comparison with those from the control site. The trace and major element variations show some slight decreasing concentration with increase distance from the factory site for mostly Pb, Zn Cu, Ni for the trace elements and Ca for the major element. There is no significant variation in the soil profile with depth for the elements. Generally, concentration of elements is in the order: Zn>Pb>Ni>Cu and Fe>Al>Ca>Mg>Na>K for the trace and major elements respectively. Computation of geo-accumulation index for the soils revealed no secondary enrichment. Application of R-mode factor analysis shows four groupings, reflecting lithological and environmental controls. The stream sediments show generally low concentrations that fall within the concentration range of sediments of similar provenance elsewhere. Metal concentration levels in the water show higher values for the surface water. Both hydrophysical and chemical parameters have slight elevated values when compared with the control and reflect a dominant geogenic source. Generally, they lie within the ambits of the World Health Organization (WHO) Standards of water quality and pose no threat to aquatic or human community. "